Kadirun Yahya: Perjalanan Menuju Saidi Syekh dalam Tarekat Naqsyabandiyah Kholidiyah - Fakhriati Fakhriati (Jurnal Lektur Keagamaan, 2013)
Naqsyabandiyah Khalidiyah Order is a name for Naqsyabandiyah order that refers to one of Caliph that is Syekh Abdul Khalik Fajduani. This School of thought has spread out in the archipelago and became a great interest for the Colonial. Kadirun Yahya who has interests with this order (tarekat) is a scientist, a physics teacher, joined tarekat and become the leader of this order and succeeded in developing and raising the Naqsyabandiyah Khalidiyah. In his hand, the Naqsyabandiyah order has different appearance instead of other tarekat. The specification of this tarekat was lies with its scientific approach. He tries to explain his tarekat through scientific theory, though he admitted that it is not easy for everybody to understand the metaphysical problems through the explanation of science, unless for they who understand religion as much as science and technology. Keywords: Tarekat, Metaphisyc, Scientific Approach